(untitled) (Research, Society and Development, 2021)
Objective: To identify the knowledge of users of a teaching hospital about the care that contributes to patient safety. Method: Descriptive, qualitative study, data collection took place from December / 2018 to January / 2019 using an instrument containing closed and open questions with 72 patients admitted to the Medical and Surgical clinics of a teaching hospital. The first hospitalization users with a minimum stay of 24 hours and over 18 years of age were included in the study. Users were excluded during data collection who were clinically unstable, with a lower level of consciousness or with an internal transfer schedule or to other units. The data were analyzed using Bardin’s content analysis. Results: The term patient safety was unknown to 47 (65.3%) of the interviewees, as for the identification of the patient (95.8%) stated that their names were questioned before any procedure. After the analysis, three major categories emerged, namely: “Patient Care and Safety”; "Dialogue with the team" and "Confirmation of procedures and trust". Conclusion: It is inferred that the patient safety culture is poorly understood by the users of the studied hospital, which suggests the need for investments on the part of managers, in addition to the effective participation of professionals in the process of empowering users in order to reduce concepts and misperceptions about safe health care.